The CRF1 Antagonist Verucerfont in Anxious Alcohol-Dependent Women: Translation of Neuroendocrine, But not of Anti-Craving Effects - Schwandt, Melanie L; Cortes, Carlos R; Kwako, Laura E; George, David T; Momenan, Reza; Sinha, Rajita; Grigoriadis, Dimitri E; Pich, Emilio Merlo; Leggio, Lorenzo; Heilig, Markus (Neuropsychopharmacology (New York, N.Y.), 2016)
Blockade of corticotropin-releasing factor receptor 1 (CRF1) suppresses stress-induced alcohol seeking in rodents, but clinical translation remains. Here, we first showed that the CRF1 antagonist verucerfont potently blocks hypothalamic-pituitary adrenal (HPA) axis activation in adrenalectomized rats. We then evaluated verucerfont for its ability to block HPA axis activation and reduce stress-induced alcohol craving in alcohol-dependent patients. Anxious, alcohol-dependent women (age 21-65 years, n=39) were admitted to the NIH Clinical Center and completed withdrawal treatment before enrollment if needed. One-week single-blind placebo was followed by randomized double-blind verucerfont (350 mg per day) or placebo for 3 weeks. Verucerfont effects on the HPA axis were evaluated using the dexamethasone-CRF test. Craving was evaluated using two established protocols, one that combines a social stressor with physical alcohol cue exposure, and one that uses guided imagery to present personalized stress, alcohol, or neutral stimuli. An fMRI session examined brain responses to negative affective stimuli and alcohol cues. In contrast to our recent observations with another CRF1 antagonist, pexacerfont, verucerfont potently blocked the HPA axis response to the dexamethasone-CRF test, but left alcohol craving unaffected. Right amygdala responses to negative affective stimuli were significantly attenuated by verucerfont, but responses to alcohol-associated stimuli were increased in some brain regions, including left insula. Discontinuation rates were significantly higher in the verucerfont group. Our findings provide the first translational evidence that CRF1 antagonists with slow receptor dissociation kinetics may have increased efficacy to dampen HPA axis responses. The findings do not support a clinical efficacy of CRF1 blockade in stress-induced alcohol craving and relapse.